Reclaiming Urban Settings: A Community Based Public Space - Bedour Ahmed; Basil Kamel (Oz, 2013)
The modes of production of urban spaces today have shifted from being initiated by institutional and formal production entities and has been transferred into the hands of the community. This change is widely represented in pocket urban spaces that have developed in inner cities and under bridges, overpasses, and highways. The utilization of these spaces unites the community and allows its inhabitants to reclaim public space.